Production and ptimizoation of cellulase enzyme using aspergillus niger USM AI 1 and comparison with trichoderma reesei via solid state fermentation system - Lee Chee Keong; Darah Ibrahim; Ibrahim Che Omar (2011)
Novel design solid state bioreactor, FERMSOSTAT, had been evaluated in cellulase production studies using local isolate Aspergillus niger USM AI 1 grown on sugarcane bagasse and palm kernel cake at 1 : 1 (w/w) ratio. Under optimised SSF conditions of 0.5 kg substrate; 70% (w/w) moisture content; ; aeration at 4 L/ fermented substrate for 5 min and mixing at 0.5 rpm for 5 min, about 3.4 U/g of Filter paper activity (FPase) was obtained. At the same time, comparative studies of the enzymes production under the same SSF conditions indicated that FPase produced by A. niger USM AI 1 was about 35.3% higher compared to Trichoderma reesei. This shows that the performance of this newly designed SSF bioreactor is acceptable and potentially used as prototype for larger-scale bioreactor design